2006
DOI: 10.1159/000095292
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of <i>CTLA-4 </i>Polymorphisms in Allergic Asthma

Abstract: Background: The CTLA-4 molecule is an important negative regulator of T cell activation. It is encoded on chromosome 2q33 and found to be associated with several allergic phenotypes including asthma. However, the association of CTLA-4 gene polymorphisms with allergic asthma is still controversial and therefore was the subject of this study. Methods: By PCR-RFLP, the distribution of three single nucleotide polymorphisms (SNPs), –1147 C/T, –318 C/T, and +49 A/G, was examined in 219 Polish Caucasoid patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 101 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…13 The patients were subdivided according to NHLBI/WHO guidelines into three subgroups: asthma I, mild asthma (54 individuals); asthma II, moderate asthma (52 individuals); and asthma III, severe asthma (92 individuals). Characteristics of the patients are shown in Table 1b.…”
Section: Study Populationsmentioning
confidence: 99%
“…13 The patients were subdivided according to NHLBI/WHO guidelines into three subgroups: asthma I, mild asthma (54 individuals); asthma II, moderate asthma (52 individuals); and asthma III, severe asthma (92 individuals). Characteristics of the patients are shown in Table 1b.…”
Section: Study Populationsmentioning
confidence: 99%
“…There were 11 studies on +49 A/G, 12 studies on −318 C/T, 6 studies on −1147 C/T, 5 studies on CT60 A/G, 3 studies on −1722 C/T and rs926169. There were 10 studies of Asians [15], [17], [25][27], [29], [32], [34], [37], [38] and 6 studies of Caucasians [16], [28], [30], [31], [33], [36]. Five studies were performed in adults [15][17], [34], [38], 11 studies in children [25][27], [29]–[32], [34][37].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were performed in adults [15][17], [34], [38], 11 studies in children [25][27], [29]–[32], [34][37]. Two studies included both adults and juveniles [28], [33]. Five studies included only atopic asthma patients [27], [28], [34], [35], [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 However, other authors have found no associations with asthma or atopy. [13][14][15] We investigated whether polymorphisms in the CTLA-4 promoter (À318) and exon 1 (þ49) are associated with susceptibility to asthma and its clinical features in Korean children.…”
Section: Introductionmentioning
confidence: 99%